Antibacterial Activity of Pediocin and Pediocin-Producing Bacteria Against Listeria monocytogenes in Meat Products - Khorshidian, Nasim; Khanniri, Elham; Mohammadi, Mehrdad; Mortazavian, Amir M.; Yousefi, Mojtaba (Frontiers in Microbiology, 2021)
One of the most important challenges in the food industry is to produce healthy and safe food products and this could be achieved through various processes as well as the use of different additives, especially chemical preservatives. However, consumer awareness and concern about chemical preservatives have led researchers to focus on the use of natural antimicrobial compounds such as bacteriocins. Pediocins which are belonged to subclass IIa of bacteriocin characterized as small unmodified peptides with a low molecular weight (2.7-17 KDa) that produced by some of Pediococcus bacteria. Pediocin and pediocin-like bacteriocins exert broad spectrum of antimicrobial activity against Gram-positive bacteria, especially against pathogenic bacteria, such as Listeria monocytogenes through formation of pores in cytoplasmic membrane and cell membrane dysfunction. Pediocins are sensitive to the most proteases enzymes such as papain, pepsin and trypsin, however, they keep their antimicrobial activity during heat treatment, low temperatures even at -80°C and after treatments with lipase, lysozyme, phospholipase C, DNase, or RNase. Due to anti-listeria activity of pediocin on the one hand and the potential health hazards associated with consumption of meat products on the other hand, this reviewed aimed to investigate the possible application of pediocin in preservation of meat and meat products against L. monocytogenes